Controlled Delivery of MicroRNAs into Primary Cells Using Nanostraw Technology. Issue 6 (19th June 2021) - Pop, Mara A.; Almquist, Benjamin D.
Abstract : Nanobiotechnology This cover image artistically depicts the controlled dosage and ratiometric delivery of small microRNAs into primary human cells using nanostraws. The nanostraws are the sidechains of the RNA in the central strand, injecting into cells, and drawing similarities to how a conductor controls the volume levels of various instruments in an orchestra. The ability to control the delivery of microRNAs is crucial as they have dosage‐dependent functions. In article number 2000061, Mara A. Pop and Benjamin D. Almquist present an approach based on a nanostraw–electroporation delivery platform that decouples the delivery from biological mechanisms to enable precise control over the amount of miRNA delivered.